The Role of Fintech Adoption in Enhancing Financial Literacy and Financial Well-Being in Emerging Markets - Larasati Dewi Anggraini; Aditya Rama Santoso; Antonio Villanueva Reyes (Lembaga Publikasi Ilmiah Nusantara, 2025)
Fintech adoption has expanded rapidly in emerging markets and reshaped how individuals access financial services. This study examines the role of fintech adoption in enhancing financial literacy and financial well-being. It focuses on emerging market contexts where digital financial services increasingly substitute traditional banking channels. The study adopts a quantitative approach and analyzes survey data collected from fintech users in emerging economies. Fintech adoption is measured through usage of digital payments, mobile banking, and financial applications. Financial literacy is captured through knowledge, skills, and confidence in managing digital financial products. Financial well-being reflects perceived financial security, control, and satisfaction. The findings show that fintech adoption has a direct positive effect on financial literacy. Higher financial literacy, in turn, improves financial well-being. Fintech adoption also exerts an indirect effect on financial well-being through financial literacy, confirming its mediating role. These results support prior evidence that digital financial tools enhance inclusion and capability when users understand how to utilize them effectively (Zhang & Fan, 2024; Bushra & Mir, 2024). The study contributes to the fintech and financial inclusion literature by clarifying the mechanism linking technology adoption and individual welfare. Practical implications highlight the need for policies that integrate fintech development with financial education initiatives.